"So hard not to feel blamed!": Assessment of implementation of Benin's Maternal and Perinatal Death Surveillance and Response strategy from 2016–2018. (27th December 2021) - Boyi Hounsou, Christelle; Agossou, Mahugnon C.U.; Bello, Kéfilath; Delvaux, Thérèse; Benova, Lenka; Vigan Guézodjè, Armelle; Hounkpatin, Hashim; Dossou, Jean‐Paul
Abstract: Objective: To assess the implementation of the Maternal and Perinatal Death Surveillance and Response (MPDSR) strategy institutionalized in Benin in 2013 to address the alarmingly high maternal and neonatal death rates. Methods: A retrospective, mixed‐methods study was performed. We used all maternal and neonatal death notifications and reviews from 2016 to 2018, reviewed the reports of 63 MPDSR working groups, and held two online group discussions. Descriptive quantitative analysis was performed, and content analysis was applied to qualitative data. Results: Deaths were under‐notified, with estimated notification rates at 46%–48% for maternal and 16%–21% for neonatal deaths over the 3 years. Review completion rates were low, corresponding to 50%–56% of maternal and 8%–17% of neonatal deaths. Causes of undernotification included very low notification of community‐based and private health facility deaths, and fear of blame. Low review completion rates were due to heavy workload, staffing shortages, fear of blame, and weak leadership. Moreover, reviews were of poor quality and the response was weak. Conclusion: Maternal and Perinatal Death Surveillance and Response is operational in Benin. However, this assessment highlights the need to strengthen the notification strategy, continuously build MPDSR committee members' capacities, engage decision‐makers for an effective response, and create a better blame‐free, accountable, and learning culture. Synopsis: There is a need to strengthen the Maternal and Perinatal Death Surveillance and Response strategy in Benin, with an emphasis on developing a blame‐free culture.